COMMUNITY CONNECTIVITY : BUILDING THE INTERNET FROM SCRATCH: ANNUAL REPORT OF THE UN IGF DYNAMIC COALITION ON COMMUNITY CONNECTIVITY - BELLI, LUCA (RIO DE JANEIRO FGV-DIREITO, 2016)
Over four billion people are currently unconnected to the Internet, including around a billion individuals who do not have access to basic telephony services. The IGF Dynamic Coalition on Community Connectivity (DC3) promotes sustainable connectivity, fostering the role of the commons in networks and the elaboration of appropriate frameworks to empower communities and individuals through connectivity. Community networks are a subset of crowdsourced networks, structured to be open, free, and neutral. Such networks rely on the active participation of local communities in the design, development, deployment and management of the shared infrastructure as a common. This Report explores several dimensions of the community network debate. The Report and the Declaration on Community Connectivity are the official outcomes produced by the DC3 in 2016. The Report includes a selection of analyses of different community connectivity issues. Submissions have been evaluated for their novelty and undertook a blind peer-review process. The Declaration on Community Connectivity is included in this Report, as a conclusion.
INGLÊS
Keywords: INTERNET; TECNOLOGIA DA INFORMACAO; REDES NEURAIS (COMPUTACAO); GERAL; LIVRO ELETRONICO / EBOOK